Penerapan Blended Learning dengan Whatsapp untuk Meningkatkan Pemahaman Konsep pada Materi Kelistrikan Di SMK Negeri 2 Kendari - Asdar, Nur Fadhilah; Arisona, Arisona; Eso, Rosliana (Jurusan Pendidikan Fisika, 2020)
The aim of study is to investigate the impact whatsapp-blended learning implementation of SMKN 2 Kendari student’s understanding of electricity learning. The study is quantitative research with pre-experimental way while using one group pretest-posttest design of research. Moreover, a research sample is taken by the method of probability sampling which is kind of simple random sampling. A technique of data collecting uses to test and non-test (questioner). A technique of data analysis uses descriptive statistic and inferential statistic. The results of this study show that the average value of student’s abilities to understand the physic concept on pre-test which is representatively 43.72, while in the post-test it is 88.00 while in the post-test it is 88.00 with an average n-gain of 0.78. The study shows that blended learning application generally takes a great response of students, which stood on 64.48% of the average scores.